Data Security Application using Rivest Cipher 6 (RC 6) Algorithm - Rahim, Robbi (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
The prevention of misuse of data by other parties requires a good data security system. Cryptography is a means of securing data with a view to maintaining confidentiality of information contained in the data, so that information cannot be known to unauthorized parties. RC6 is a cryptographic block cipher algorithm that can be used to secure data or files from irresponsible parties. This study found that the data secured using the RC6 algorithm was quite good and required a long time for some parties to get the plain text.